Mechanism of Toxicity and Tolerance in Plants Against Aluminum Stress - Robiatul Adawiyah; Musadia Afa (Agrotech Journal, 2019)
Aluminum (Al 3+) is rhizotoxic ions in the soil (mineral) acid. Al activities increases with increasing soil acidity, below pH 5.5 the solubility of Al 3+ cations will increase. High level of soluble can cause interference with metabolic processes and plant physiology. Cumulatively, the physiology of metabolic disorders and initially looked at the root system. The tip of the root and lateral roots become thickened and hair and roots become lower, causing a decrease in root length and root tissue enlargement thus inhibiting the growth of roots, the absorption of nutrients and water, will further lower the growth, production and productivity of crops. Although Al disrupt metabolism and suppress the growth of the plant, until a certain threshold of adverse effects in Al still be tolerated, depending on the type of plant and the level of activity of Al. Tolerance of crops to Al can be expressed through two mechanisms, namely: external tolerance mechanism and internal tolerance mechanism. The main difference between the two mechanisms is in the area of detoxification Al whether in symplast (internal) or apoplast (exclusion). The ability of plants to be able to adapt to drought stress Al, depends on the ability of plants to produce organic acid in an amount sufficient for eliminating the toxic influence of stress Al. Root exudates of plants capable of producing such an organic acid that plays an important role in adaptation strategies. The high production of organic acids is associated with the formation of specific enzymes, as a response to stress Al. Allegedly the sensitive strain, the synthesis of organic acids is not adequate to chelate Al